Irritant contact dermatitis caused by sap of rengas - Betty Ekawati Suryaningsih (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2019)
Irritant contact dermatitis (ICD) is an inflammation of skin caused by direct cytotoxic effects of chemical, physical or biological agents on epidermal cells without a presence of specific antibody production. It was reported that a 40-year-old man, complaining of itching and a burned sensation on his skins accompanied by pain after contaminated by sap of Rengas. Diagnosis of ICD was established by history taking and physical examination: there are erythematous, multiple, discrete papules, partly necrotic-erythematous skin base on his forearm and right lower abdomen. The patient was treated with mometasone furoate smeared and antihistamines once a night. A characteristic of the sap is black on its woods. Compounds of the sap contain ursiol, rengol, glutarengol, laccol and thitsiol that are irritants causing the ICD.